0520 Blood Pressure Effects of Positive Airway Pressure Treatment in Obese and Non-obese Adults with Obstructive Sleep Apnea. (27th April 2018) - Kuna, S T; Townsend, R R; Keenan, B; Maislin, D; Sif Arnardottir, E; Gislason, T; Benediktsdottir, B; Gudmundsdottir, S; Sifferman, A; Staley, B; Pack, F M; Guo, X; et al.
Abstract: Introduction: Numerous studies have demonstrated that positive airway pressure (PAP) treatment of patients with obstructive sleep apnea (OSA) reduces blood pressure (BP), possibly by decreasing sympathetic activity. Obesity is a risk factor for OSA and hypertension and is characterized by increased sympathetic activity. In this study, we evaluated the impact of obesity on the BP response to PAP treatment in obese and non-obese OSA adults and the role of sympathetic activity in contributing to the BP response. Methods: We classified 188 subjects with OSA as obese (n=119) based on waist circumference (>107 cm in men and >96 cm in women) or non-obese (n=69). Participants underwent 24-hr ambulatory blood pressure monitoring (ABPM) and a 24-hr urinary catecholamine collection before and following 4 months of PAP treatment. Results: Baseline apnea-hypopnea index was 37.3 ± 17.1[SD] and 34.2 ± 13.3 events/hr for obese and non-obese participants. There were no significant differences between groups in 24-hr mean arterial pressure (MAP, p=0.075) or 24-hr catecholamine excretion at baseline (p=0.769). Comparing changes from baseline between obese (n=65) and non-obese (n=35) OSA subjects adherent to PAP treatment, the two groups did not differ in the change in MAP (p=0.329), but the obese group had a greater reduction in nocturnal MAP (p=0.021), nocturnal diastolic BP (p =0.004), nocturnal-to-daytime ratios of MAP (p=0.043) and nocturnal diastolic BP (p=0.016). Mean 24-hr urinary norepinephrine decreased by 5.79 ng/mg creatinine (95% CI 8.04 to 3.54; p=0.0001) in obese OSA subjects, but no significant reduction occurred in non-obese OSA subjects. No significant relationship was observed between changes in log-transformed 24-hr urinary norepinephrine and changes in any ABPM measure. Conclusion: Compared to non-obese adults with OSA, obese adults with OSA had greater reductions in several nocturnal BP measures following 4 months of PAP treatment; however, these changes were not related to the large reduction in 24-hr urinary norepinephrine following PAP treatment in the obese group. Further studies are required to assess the physiologic basis of BP reduction induced by PAP in obese and non-obese OSA patients. Support (If Any): NIH 1P01-1HL094307.